The use of risk budgets in portfolio optimization - Unger, Albina (Springer Fachmedien Wiesbaden Imprint: Springer Gabler, 2015)
Risk budgeting models set risk diversification as objective in portfolio allocation and are mainly promoted from the asset management industry. Albina Unger examines the portfolios based on different risk measures in several aspects from the academic perspective (Utility, Performance, Risk, Different Market Phases, Robustness, and Factor Exposures) to investigate the use of these models for asset allocation. Beside the risk budgeting models, alternatives of risk-based investment styles are also presented and examined. The results show that equalizing the risk across the assets does not prevent losses, especially in crisis periods and the performance can mainly be explained by exposures to known asset pricing factors. Thus, the advantages of these approaches compared to known minimum risk portfolios are doubtful.  Contents Theoretical Background Alternative Approaches in Portfolio Management Minimum Risk Portfolios Risk Budgeting Portfolios Robustness Factor Models  Target Groups Researchers and students in the field of economics with a focus on finance and financial economics Finance/investment professionals  The Author Albina Unger holds a doctoral degree from the Faculty of Finance at the University of Bremen, Germany. She now works as a risk manager.